Development of a core set of single nucleotide polymorphism markers for genetic diversity analysis and cultivar fingerprinting in cowpea. Issue 3 (5th May 2021) - Wu, Xinyi; Wang, Baogen; Wu, Suqi; Li, Sujuan; Zhang, Yan; Wang, Ying; Li, Yanwei; Wang, Jian; Wu, Xiaohua; Lu, Zhongfu; Li, Guojing
Abstract: Cowpea is an important legume crop worldwide. However, the diversity and relationship of current accessions remain unclear due to a lack of robust genetic information. A set of 40, 089 single nucleotide polymorphisms (SNPs) adapted to the Kompetitive Allele Specific PCR (KASP) SNP genotyping platform were developed from the existing Illumina Cowpea iSelect Consortium Array for cowpea germplasm genetic diversity assessment and variety identification. Using the genotypic data of 299 cowpea accessions obtained from this SNP assay, a precore pool of 434 SNPs and 50 informative core SNPs was selected and validated for use in future genetic diversity analyses of cowpea germplasm. By further genotyping 75 commercial cultivars using the set of 50 core SNPs, pairwise genotype alignment and dendrogram analysis both showed that each cultivar could be uniquely identified by this core set of markers. The KASP markers developed in this study provide a flexible marker resource for both basic and applied research of cowpea. The precore SNP pool and the core SNP set also provide valuable tools for genetic variation assessment and variety rights protection for cowpea breeders.